1984
DOI: 10.1111/j.1432-1033.1984.tb08119.x
|View full text |Cite
|
Sign up to set email alerts
|

Diamine-induced dissociation of the first component of human complement, C1

Abstract: Lysine has been shown to inhibit spontaneous and antibody-dependent C1 activation. This paper demonstrates that lysine does not prevent autoactivation of purified Clr. 20 mM lysine, 1,2-diaminoethane, 1,3-diaminopropane, 1,Cdiaminobutane or 1,5-diaminopentane are able to dissociate C1 into its two entities, C l q and the calciumdependent Clr,-Cls, complex. Ig-ovalbumin insoluble complexes bearing C1 are also dissociated by lysine and the above-mentioned diamines used at the same concentration: Clq remains boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
9
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(10 reference statements)
5
9
0
Order By: Relevance
“…4) for the calcium-dependent dimerization of Cls, which occurs in the absence of Clr (6,7,11,17). It (4,25). In agreement with comparative neutron diffraction studies on Clq and C1 (26), this led us to the conclusion that in the Cl complex the (Cir, Cls)2 subunit adopts a nonlinear conformation corresponding to its activatable state.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…4) for the calcium-dependent dimerization of Cls, which occurs in the absence of Clr (6,7,11,17). It (4,25). In agreement with comparative neutron diffraction studies on Clq and C1 (26), this led us to the conclusion that in the Cl complex the (Cir, Cls)2 subunit adopts a nonlinear conformation corresponding to its activatable state.…”
Section: Methodssupporting
confidence: 76%
“…Clq is considered as the recognition subunit and its structure has been elucidated by chemical and electron microscopic studies (1,2). (Cir, Cls)2, the catalytic subunit, is released from C1 by treatment with citrate (3) or diamino compounds (4) or at high ionic strength (5). Subcomponents Cir and Cls are both serine proteases that, at the monomeric level, appear very similar: the zymogen forms are both single-chain proteins of molecular weights ranging from 83,000 to 95,000, converted on activation into two disulfide-linked polypeptide chains, A and B, of respective molecular weights 58,000 and 28,000-35,000 (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In these conditions, the calcium ions present in the Clr2-Cls2 complex appear inaccessible to chelators such as EDTA, and Clr is removed from the adsorbent only by lowering the pH to 5.0. Recently, dissociation of Cl by diam ines has been demonstrated [14], in the pres ence of 20mM lysine, 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane or 1,5-diaminopentane ( fig. 1).…”
Section: Evidence For Two Distinct Entities In CLmentioning
confidence: 99%
“…We do not yet know if early steps in CCP activation or steps in MAC formation are impaired by spermine, but we suggest that spermine masks sites on the bacterial surface which influence either one or both processes. Since previous work documented the ability of spermine to dissociate the C1 complex (38), it is likely that the capacity of 8 mM spermine to significantly reduce the bactericidal effect of NHS and to abolish C8 binding to whole gonococci can be explained by this mechanism. Clearly, however, the results from our hemolytic assays using antibody-sensitized sheep blood erythrocytes indicate that residual CCP activity remains in such serum but that the level is insufficient to kill bacteria.…”
Section: Vol 78 2010 Polyamines and Antimicrobial Resistance In Gonmentioning
confidence: 99%
“…The capacity of spermine to inhibit NHS-mediated activity against gonococci and E. coli suggested that its presence in the SBA influenced CCP activity. Indeed, earlier studies that used 20 mM or greater concentrations of spermine showed that this polyamine can inhibit the formation of the C1 complex and prevent activation of the downstream CCP cascade (10,20,38). Using a modified protocol of the EZ complement CH50 test (Diamedix, Miami, FL), we found that 8 mM spermine, but not 1 mM spermine, significantly decreased the hemolytic activity of 1% (vol/vol) but not 10% (vol/vol) NHS against antibodysensitized sheep erythrocytes (Fig.…”
Section: Vol 78 2010 Polyamines and Antimicrobial Resistance In Gonmentioning
confidence: 99%